Understanding the relationship between the Proteus effect, immersion, and gender among World of Warcraft players: An empirical survey study. Issue 8 (11th June 2021) - Stavropoulos, Vasileios; Rennie, John; Morcos, Maria; Gomez, Rapson; Griffiths, Mark D.
ABSTRACT: Online gaming is part of contemporary life, with a range of influences on gamer's behaviour. The convergence and alignment of an individual's attitude and behaviour with features and characteristics of their in-game representation (i.e. their avatar), is conceptualised as the 'Proteus effect' (PE). In the massively multiplayer online role-playing game World of Warcraft ( WoW ), the Draenei ('exiled ones') are one type of in-game character faction. In the present study, the interplay between choosing the class of Draenei, experiencing game-related immersion, along with the gamer's biological gender was examined in relation to PE behaviours among 404 WoW gamers (males = 299; 74%; females = 104; 26%). Participants completed the Proteus Effect Scale and the Immersion sub-scale of the User-Avatar Questionnaire. A hierarchical regression analysis indicated a significant positive association between immersion and PE behaviours. Furthermore, mediation and moderated mediation analyses suggested that being a Draenei was positively associated with the level of game-related immersion, which in turn associated to higher PE behaviours offline, independent of participants' gender. Results indicate that gamers who are more immersed within the gaming world tend to exhibit elevated PE behaviours. Moreover, being a Draenei in WoW appeared to relate with higher game-immersion experiences, which resulted in higher PE behaviours offline.